An Analysis of Figurative Languages Used in Disney Songs’ Lyrics by Naomi Scott and John Legend Featuring Ariana Grande - Ramadhani, Elvia; Fitriana, Eka; Isnaini, Muh.; Nuriadi (Journal of English Education Forum (JEEF), 2024)
The research delves into the fascinating world of Disney songs and their use of figurative language, exploring how this impacts children's language skills and creativity. With the aim of closely analyzing three specific Disney songs, the study seeks to uncover how these beloved tunes effectively utilize different forms of figurative language to communicate important moral values. Through careful examination, the study identifies five key types of figurative language present in these songs: metaphor, simile, personification, hyperbole, and paradox. By taking a closer look at how Disney songs employ these various forms of figurative language to convey deeper messages that resonate with audiences, educators can gain valuable insights into using music as a powerful tool for facilitating language development and promoting moral understanding in young children. The study emphasizes the potential role that beloved Disney songs can play as effective educational tools for fostering greater comprehension of language and encouraging strong moral values among young audiences. Overall, this research serves as a valuable reminder of the importance of creative expression in education - demonstrating how even something as seemingly simple as a catchy tune can have profound impacts on children's cognitive and emotional development.